Little Core Based System on Chip Platform for Internet of Thing - Sang Don Kim; Seung Eun Lee (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Although the technology scaling has enabled designers to integrate a large number of hardware blocks onto a single chip realizing System on Chip (SoC), problems arising from leakage current have made power reduction an important issue. The IoT platform has restricted power consumption because of battery power. In this paper, we propose our little core based IoT platform focusing on the low power and expandability. The experimental results demonstrate the feasibility of our proposal to the IoT.